2021
DOI: 10.1371/journal.pntd.0009997
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virological impact of single and dual infections with influenza A (H1N1) and SARS-CoV-2 in adult inpatients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mimics the influenza A (H1N1) virus in terms of clinical presentation, transmission mechanism, and seasonal coincidence. Comprehensive data for the clinical severity of adult patients co-infected by both H1N1 and SARS-CoV-2, and, particularly, the relationship with PCR cycle threshold (Ct) values are not yet available. All participants in this study were tested for H1N1 and SARS-CoV-2 simultaneously at admission. Demographic, clinical, treatment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…The total number of SARS-CoV-2 patients co-infected with influenza/RSV and mono-infected patients per study ranged from 22 to 4501. Nine studies were mainly conducted in Asia, six of which were from China [ 16 , 17 , 21 - 23 , 25 ]. For viral detection method, SARS-CoV-2 was detected using PCR for all studies whereas influenza and / or RSV co-infection was confirmed by PCR, serological testing, or antigen assays.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of SARS-CoV-2 patients co-infected with influenza/RSV and mono-infected patients per study ranged from 22 to 4501. Nine studies were mainly conducted in Asia, six of which were from China [ 16 , 17 , 21 - 23 , 25 ]. For viral detection method, SARS-CoV-2 was detected using PCR for all studies whereas influenza and / or RSV co-infection was confirmed by PCR, serological testing, or antigen assays.…”
Section: Resultsmentioning
confidence: 99%
“…Different extracts of black elderberry ( S. nigra ) [ 19 , 20 ] and black chokeberry ( A. melanocarpa ) [ 21 ] are known for their health-promoting antimicrobial properties that have been used for a long time in folk medicine and in the food industry. These plants owe their properties mainly to the high content of various polyphenols [ 22 , 23 , 24 ]. Here, we demonstrate the antiviral activity of an originally developed blend of double-standardized extracts of A. melanocarpa and S. nigra (EAM-ESN) and its individual components against the human respiratory viruses influenza virus A/H1N1 and betacoronavirus HCoV-OC43, belonging to the β-coronaviruses as the current pandemic SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus infections and influenza share similar “influenza-like” clinical manifestations usually of mild or moderate course. However, simultaneous infections might result in a big challenge in controlling both diseases, as it is currently observed for the COVID-19 pandemic and seasonal influenza [ 24 ]. Betacoronaviruses and influenza viruses are droplet-borne pathogens that invade the upper or lower respiratory tract by binding to specific cell surface receptors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the relatively low prevalence (approximately 2.0%) in the State of Sergipe, our findings add to the growing body of evidence on the severity of SARS-CoV-2 and influenza A (H3N2) virus coinfection. Recent observational studies reported that coinfection with SARS-CoV-2 and influenza A (H1N1) predominantly affected older people and were associated with poorer clinical outcomes 4 , 5 . However, mortality data from meta-analyses showed conflicting results because of between-study heterogeneity 6 , 7 .…”
mentioning
confidence: 99%